Pendekatan kontekstual berbantuan software geogebra untuk meningkatkan kemampuan komunikasi matematis siswa SMP kelas VIII - Nurjanah, Siti; Afrilianto, M; Purwasih, Ratni (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2025)
This research seeks to enchance the mathematical communication skills of eight-grade junior high school students by implementing a contextual approach supported by Geogebra software. The research method employed is a quasi-experimental with a nonequivalent control group. Data collection techniques in this study involved using intruments in the form of mathematical communication skills tests and interview. The sampling technique employed was purposive sampling. The research sample consisted of 34 students from class VIII-E and 34 students from class VIII-I. The data analysis techniques included data gathering, data analisysis, data visualization, and drawing conclusions using SPSS 25. The conclusion drawn from this study is that the improvement in mathematical communication skills among students taught using the contextual approach supported using Geogebra software is more effective than those taught using conventional methods. This study not only focus on the final results but also considers the entire learning process to achieve a comprehensive and accurate assessment